2010
DOI: 10.1007/s10654-010-9472-2
|View full text |Cite
|
Sign up to set email alerts
|

Health factors and longevity in men and women: a 26-year follow-up study

Abstract: No. of words: (main text including references) 2713Words in Abstract: 249 Tables: 3 References: 27 Abstract Health factors have the power to prevent and postpone diseases and death; however, studies using the same methodology in both men and women are sparse. We aimed to study the ability of health factors to prevent mortality in a population-based, 26-year follow-up of Swedish men and women.During 1969-70, a health-screening programme was offered to a stratified sample of 3064 individuals aged 18-64 years t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…The difference in prevalence could be due to more particles in the air in Stockholm, higher proportion of smokers or a higher awareness of COPD in recent years. Prevalence of diagnosed COPD increased dramatically among persons aged between 45–84 years whereas it decreased among persons aged 85 years and over which may be explained by the effect of smoking on longevity [16]. The opposite was observed for the prevalence of anxiety /phobia which was high in young adults aged between 18–44 years (6.6%).…”
Section: Discussionmentioning
confidence: 99%
“…The difference in prevalence could be due to more particles in the air in Stockholm, higher proportion of smokers or a higher awareness of COPD in recent years. Prevalence of diagnosed COPD increased dramatically among persons aged between 45–84 years whereas it decreased among persons aged 85 years and over which may be explained by the effect of smoking on longevity [16]. The opposite was observed for the prevalence of anxiety /phobia which was high in young adults aged between 18–44 years (6.6%).…”
Section: Discussionmentioning
confidence: 99%
“…The incentive to spend money on healthy foods and time on physical activity may also be reduced in individuals without cash margins as they are primarily concerned with financial worries, rather than health matters [13,30-32]. …”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown that men and women may be affected differently in their contacts with health care if they are single or living with a partner, where single men have been shown to be vulnerable and less likely to seek healthcare [11,12]. Moreover, men and women have been shown to have different lifestyle patterns and divergent risks for cardiovascular disease and mortality [13,14], which suggest that they should be studied independently.…”
Section: Introductionmentioning
confidence: 99%
“…Certain groups may experience aging and health differently from others. The most obvious instance is gender: older men and women have been observed to have different lifespans [1, 2], functional trajectories [3], risk factors for disease [4], chronic and acute diseases [5, 6], and use of medical treatments [7]. There is practical and theoretical importance in understanding health changes during aging, especially the maintenance of health and the ability to recuperate from sickness, differ between men and women.…”
Section: Introductionmentioning
confidence: 99%